2009
DOI: 10.1038/ajg.2009.163
|View full text |Cite
|
Sign up to set email alerts
|

Novel Genetic Risk Markers for Ulcerative Colitis in the IL2/IL21 Region Are in Epistasis With IL23R and Suggest a Common Genetic Background for Ulcerative Colitis and Celiac Disease

Abstract: Similar to other autoimmune diseases such as celiac disease, rheumatoid arthritis, type 1 diabetes, Graves' disease, and psoriatic arthritis, genetic variation in the chromosome 4q27 region predisposes to UC, suggesting a common genetic background for these diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
72
0
3

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 79 publications
(77 citation statements)
references
References 50 publications
2
72
0
3
Order By: Relevance
“…Upregulation of IL-15 expression by epithelial cells and dendritic cells in the lamina propria seems to also contribute to the altered signaling properties of the CD8+ T cell population (16). In addition, recent genome-wide association studies have provided convincing evidence that the IL-21 gene also is associated with CD (19,20). IL-21 has been shown to stimulate epithelial cells to secrete chemokines, to facilitate the recruitment of immune cells within the inflamed tissue and to modulate the proliferation and function of CD8 + T and NK cells (21).…”
Section: Ppar Signaling Pathway and Cancer-related Proteins Are Involmentioning
confidence: 88%
“…Upregulation of IL-15 expression by epithelial cells and dendritic cells in the lamina propria seems to also contribute to the altered signaling properties of the CD8+ T cell population (16). In addition, recent genome-wide association studies have provided convincing evidence that the IL-21 gene also is associated with CD (19,20). IL-21 has been shown to stimulate epithelial cells to secrete chemokines, to facilitate the recruitment of immune cells within the inflamed tissue and to modulate the proliferation and function of CD8 + T and NK cells (21).…”
Section: Ppar Signaling Pathway and Cancer-related Proteins Are Involmentioning
confidence: 88%
“…Evidence concerning the involvement of a specific variant in this region was not possible due to strong LD in the region. Interestingly, this region has also been shown to associate with type Ⅰ diabetes, rheumatoid arthritis and recently UC, hinting at the presence of a common factor for immune-mediated diseases [115][116][117] . To increase the likelihood of disease-gene identification in this GWAS data, additional non-HLA SNPs were subsequently subjected to genotyping in an even larger replication panel [113,114] .…”
Section: Celiac Diseasementioning
confidence: 99%
“…Accordingly the signature cytokines of Th17 cells (IL-17A, IL-17F, IL-22) are produced in the intestine of CD and UC patients [116,[118][119][120]. Additionally, genome wide association studies have linked polymorphism in Th17-related genes, such as IL-23R and STAT3 with IBD [121][122][123][124]. In line with these associations murine studies have also shown that Th17 cells are involved in numerous autoimmune and chronic inflammatory diseases [2], and IBD is one of these diseases [125]: ROR t deficient mice, which lack Th17 cells, exhibit attenuated experimentally induced autoimmune disease [4].…”
Section: Breakdown Of the Immune Homeostasis In The Intestinementioning
confidence: 99%